PGE2 MEDIATES OENOCYTOID CELL LYSIS VIA A SODIUM‐POTASSIUM‐CHLORIDE COTRANSPORTER. Issue 4 (6th April 2015) - Shrestha, Sony; Park, Jiyeong; Ahn, Seung‐Joon; Kim, Yonggyun
<x xml:space="preserve">Abstract</x> Prostaglandin E2 (PGE2) mediates immune responses of the beet armyworm, Spodoptera exigua, including oenocytoid cell lysis (a class of lepidopteran hemocytes: OCL) via its specific membrane receptor to release inactive prophenoloxidase (PPO) into hemolymph. PPO is activated into phenoloxidase in the plasma to play crucial roles in the immune responses of S. exigua. The mechanism of OCL has not been elucidated, however we posed the hypothesis that a rapid accumulation of sodium ions within the oenocytoids allows a massive influx of water by the ion gradient, which leads to the cell lysis. It remains unclear which sodium channel is responsible for the OCL in response to PGE2. This study identified a specific sodium channel called sodium‐potassium‐chloride cotransporter 1 (Se‐NKCC1) expressed in hemocytes of S. exigua and analyzed its function in the OCL in response to PGE2. Se‐NKCC1 encodes a basic membrane protein (pI value = 8.445) of 1, 066 amino acid residues, which contains 12 putative transmembrane domains. Se‐NKCC1 was expressed in all developmental stages and tissues. qPCR showed that bacterial challenge significantly induced its expression. A specific inhibitor of NKCC, bumetanide, prevented the OCL in a dose‐dependent manner. When RNA interference (RNAi) using double‐stranded RNA specific to Se‐NKCC1 suppressed its expression, the OCL and PPO activation were significantly inhibited in response to PGE2. The RNAi treatment also reduced nodule formation to bacterial challenge. These results suggest that Se‐NKCC1 is associated with OCL by facilitating inward transport of ions in response to PGE2.